Immunosuppressive IDO in Cancer: Mechanisms of Action, Animal Models, and Targeting Strategies - Zhai, Lijie; Bell, April; Ladomersky, Erik; Lauing, Kristen L.; Bollu, Lakshmi; Sosman, Jeffrey A.; Zhang, Bin; Wu, Jennifer D.; Miller, Stephen D.; Meeks, Joshua J.; Lukas, Rimas V.; Wyatt, Eugene; et al. (Frontiers in Immunology, 2020)
Indoleamine 2, 3-dioxygenase 1 (IDO; IDO1; INDO) is a rate-limiting enzyme that metabolizes the essential amino acid, tryptophan, into downstream kynurenines. Canonically, the metabolic depletion of tryptophan and/or the accumulation of kynurenine is the mechanism that defines how immunosuppressive IDO inhibits immune cell effector functions and/or facilitates T cell death. Non-canonically, IDO also suppresses immunity through non-enzymic effects. Since IDO targeting compounds predominantly aim to inhibit metabolic activity as evidenced across the numerous clinical trials currently evaluating safety/efficacy in patients with cancer, in addition to the recent disappointment of IDO enzyme inhibitor therapy during the phase III ECHO-301 trial, the issue of IDO non-enzyme effects have come to the forefront of mechanistic and therapeutic consideration(s). Here, we review enzyme-dependent and -independent IDO-mediated immunosuppression as it primarily relates to glioblastoma (GBM); the most common and aggressive primary brain tumor in adults. Our group’s recent discovery that IDO levels increase in the brain parenchyma during advanced age and regardless of whether GBM is present, highlights an immunosuppressive synergy between aging-increased IDO activity in cells of the central nervous system that reside outside of the brain tumor but collaborate with GBM cell IDO activity inside of the tumor. Because of their potential value for the in vivo study of IDO, we also review current transgenic animal modeling systems while highlighting three new constructs recently created by our group. This work converges on the central premise that maximal immunotherapeutic efficacy in subjects with advanced cancer requires both IDO enzyme- and non-enzyme-neutralization, which is not adequately addressed by available IDO-targeting pharmacologic approaches at this time.